2020
DOI: 10.1101/2020.01.13.903179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species coexistence in resource-limited patterned ecosystems is facilitated by the interplay of spatial self-organisation and intraspecific competition

Abstract: The exploration of mechanisms that enable species coexistence under competition for a sole limiting resource is widespread across ecology. One classical example is the coexistence of herbaceous and woody species in self-organised dryland vegetation patterns. Previous theoretical investigations have explained this phenomenon by making strong assumptions on the differences between grasses and trees (e.g. contrasting dispersal behaviours or different functional responses to soil moisture). Motivated by classical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…In studies of savanna ecosystems, the coexistence of grass and tree species has also been linked to self‐organised pattern formation (Baudena & Rietkerk, 2013; Gilad et al, 2007; Nathan et al, 2013). However, these studies usually assume that only one of the plant species is involved in the pattern‐forming process (notable exceptions are Eigentler, 2021; Eigentler & Sherratt, 2020)), which then facilitates the persistence of the other species. The results of the present study suggest that self‐organised pattern formation, especially when it interacts with pre‐existing β‐diversity (or spatial heterogeneity in general), might be an important mechanism complementing the well‐established theories on plant diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of savanna ecosystems, the coexistence of grass and tree species has also been linked to self‐organised pattern formation (Baudena & Rietkerk, 2013; Gilad et al, 2007; Nathan et al, 2013). However, these studies usually assume that only one of the plant species is involved in the pattern‐forming process (notable exceptions are Eigentler, 2021; Eigentler & Sherratt, 2020)), which then facilitates the persistence of the other species. The results of the present study suggest that self‐organised pattern formation, especially when it interacts with pre‐existing β‐diversity (or spatial heterogeneity in general), might be an important mechanism complementing the well‐established theories on plant diversity.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that coexistence of two plant species (grasses and trees) is possible due to a colonisation-competition trade-off. In Eigentler (2021), these results were extended to cover a wider range of environmental conditions by including intraspecific competition. In general, conditions under which pattern formation might facilitate -diversity include less strongly stabilising selection regimes, more flexible shapes of the local trait distributions (e.g.…”
Section: Increase Of -Diversity Via Self-organised Pattern Formationmentioning
confidence: 93%
“…There are also many ways that the current modelling framework can be extended. For example, the discrete model can be extended to consider multiple interacting subpopulations, and the same discrete-to-continuum averaging approach could be used to construct a continuum limit model, which would take the form of a system of coupled partial differential equation models [43,6468]. We leave this extension for future consideration.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing awareness of the limitations of classical community ecological models, e.g. Lotka-Volterra-type competition models, to predict ecosystem effects of a changing environment (Clark et al 2020;Damgaard and Weiner 2021;Eigentler 2021;Martyn et al 2020;Mayfield and Stouffer 2017;Neill et al 2009;Vellend 2010). For example, it is widely appreciated that frequencydependent species interactions, in which relatively rare species are favored over more common species, may play an important role in plant species co-existence and community dynamics in plant communities (Chisholm and Fung 2020;Connell et al 1984).…”
Section: Introductionmentioning
confidence: 99%